THE IMPORTANCE OF THE PROGRAM USMLE IN HIGHER EDUCATION - Akramovna, Fazilova Nodira (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
This article is written about the importance and effectiveness of USMLE program in higher education. In addition, the article provides information about the steps and useful aspects of the USMLE program.